2005
DOI: 10.1007/s10620-005-3028-4
|View full text |Cite
|
Sign up to set email alerts
|

Inverse Dose Effect of Pretest Dietary Lactose Intake on Breath Hydrogen Results and Symptoms in Lactase Nonpersistent Subjects

Abstract: The aim of this study was to determine a relationship between pretest intake of lactose and outcome of lactose breath hydrogen test. Patients presented at a testing laboratory participated in the study. A 3-hour breath hydrogen, 50-g lactose challenge was carried out. Results were tabulated and patients completed a 3-day recall diet questionnaire. Daily lactose intake was independently calculated and was associated with breath hydrogen and total symptom score. Statistical analysis used Spearman's correlation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 36 publications
1
18
3
Order By: Relevance
“…Total symptom scores ( 3hTSS) in group 1 were higher than in group 4 but the difference was not statistically significant ( p = 0.187). An ad hoc comparison of participants from pattern group 4 of our previous lactose study [26] with those included in this group revealed that only 9 (30%) were classified here from both studies (data not shown). Overall, women complained significantly more of symptoms than men (40/61 vs. 12/29, p = 0.04).…”
Section: Resultsmentioning
confidence: 85%
See 3 more Smart Citations
“…Total symptom scores ( 3hTSS) in group 1 were higher than in group 4 but the difference was not statistically significant ( p = 0.187). An ad hoc comparison of participants from pattern group 4 of our previous lactose study [26] with those included in this group revealed that only 9 (30%) were classified here from both studies (data not shown). Overall, women complained significantly more of symptoms than men (40/61 vs. 12/29, p = 0.04).…”
Section: Resultsmentioning
confidence: 85%
“…Many of these subjects were included in a similar study with a 50-g lactose challenge test. Those tests were performed one to four weeks apart from the current challenge and analyzed independently partly because of the different dose of sugar used [26]. In a manner similar to the results of the lactose challenge, we grouped breath hydrogen and symptom scores into four categories as outlined in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients with IBS generally do not experience a higher frequency of lactose maldigestion than the background population (27). The frequency of lactose intolerance, although most likely worse in lactose maldigestion individuals, is seen almost as frequently in LP populations (27,28). These observations have led to a more recent concept of lactose sensitivity.…”
Section: Lactose Intolerancementioning
confidence: 99%